A new quantitative method to determine the uptake of SPIONs in animal tissue and its application to determine the quantity of nanoparticles in the liver and lung of Balb-c mice exposed to the SPIONs - Zysler, Roberto Daniel (2012)
We propose a new method for determining the quantity of superparamagnetic iron oxide nanoparticles (Fe3O4, SPIONs) embedded in animal tissue using magnetization measurements. With this method, the smallest detectable quantity of magnetite nanoparticles in a tissue sample is ∼1 μg. We showed that this method has proved being efficient. In this study, we focused in determining the quantity of SPION confined in lung and liver tissue of mice injected with ∼13 nm magnetite superparamagnetic nanoparticles. Furthermore, the method allowed us to detect the magnetite nanoparticles present in animal tissues without letting the natural iron ions present in the tissue or blood interfere with the measurements.